Geo-climate effects on asthma and allergic diseases in adults in Turkey: Results of PARFAIT study - Metintas, Selma; Kurt, Emel; Basyigit, Ilknur; Bulut, Ismet; Coskun, Evsen; Dabak, Sennur; Kalyoncu, A. Fuat (Taylor and Francis Ltd., 2010)
The aim of the study was to evaluate the role of geo-climatic factors on the prevalence of allergic diseases in the adult population in Turkey. A total of 25,843 questionnaires using data from parents of 25,843 primary schoolchildren from 14 cities were evaluated. Mean annual temperature was significantly associated with the prevalence of asthma and wheezing in both sexes [respectively; OR: 1.008 (95% CI: 1.003-1.011) and OR: 1.012 (1.006-1.018 in males), OR: 1.007 (1.003-1.012) and OR: 1.01 (1.002-1.018) in females]. In addition, it was associated with eczema in females [OR: 1.007 (1.001-1.012)]. Asthma in females was associated with mean annual humidity in the air [OR: 1.001 (1.000-1.002)]. Annual number of days with snow is associated with wheezing in both sexes [respectively, OR: 1.001 (1.000-1.002) in males and OR: 1.002 (1.000-1.003) in females]. Protective measures could come into priority in certain areas of the country. Allergic diseases may increase as a cause of climate change in the future. © 2010 Taylor & Francis.
Keywords: Allergy; Asthma; Climate; Epidemiology; Health